2008
DOI: 10.1039/b717437c
|View full text |Cite
|
Sign up to set email alerts
|

Selective one-electron oxidation of duplex DNA oligomers: reaction at thymines

Abstract: The one-electron oxidation of duplex DNA generates a nucleobase radical cation (electron "hole") that migrates long distances by a hopping mechanism. The radical cation reacts irreversibly with H2O or O2 to form oxidation products (damaged bases). In normal DNA (containing the four common DNA bases), reaction occurs most frequently at guanine. However, in DNA duplexes that do not contain guanine (i.e., those comprised exclusively of A/T base pairs), we discovered that reaction occurs primarily at thymine and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(107 citation statements)
references
References 72 publications
(79 reference statements)
5
102
0
Order By: Relevance
“…This observation may be supported by previous data, however, for the induction of a T lesion, a TT sequence is necessary [31].…”
Section: '-End-t T T a A T T A T A C A T A A C A T A T A T T T A A Tsupporting
confidence: 80%
See 3 more Smart Citations
“…This observation may be supported by previous data, however, for the induction of a T lesion, a TT sequence is necessary [31].…”
Section: '-End-t T T a A T T A T A C A T A A C A T A T A T T T A A Tsupporting
confidence: 80%
“…In the case of the two other thymidine lesions located at positions T21 and T19, the neighbouring thymine was not present, which is in opposition to the above-mentioned requirement [31]. The next section of discussed strand consists of AAA accomplishing the role of shutter, which has been previously proven [30,32].…”
Section: '-End-t T T a A T T A T A C A T A A C A T A T A T T T A A Tmentioning
confidence: 50%
See 2 more Smart Citations
“…Less than a decade after discovering structural features of DNA double helix [5], the first experiments to answer how charge can be transported through DNA chains were carried out [6][7][8] but this question is still debated [9][10][11][12] and DNA was described as an insulator, semiconductor, or molecular wire. Extensive experimentation has shown that the radical cation (electron ''hole") is introduced into a duplex DNA oligomer in solution by one-electron oxidation of guanosine.…”
Section: Introductionmentioning
confidence: 99%